Engaging Students in Audiovisual Coding Through Interactive MATLAB GUIs - Carlos Cuevas; Carlos Cortes; Narciso Garcia (IEEE Access)
Traditional educational methods in higher education, such as lectures and hands-on exercises, often struggle to fully engage students or address the complexities inherent in audiovisual signal coding. This gap underscores the need for innovative educational tools that not only foster deeper understanding but also enhance student engagement within the university setting. Effective evaluation of these tools requires comprehensive assessment of both learning outcomes and user experience. This study introduces three novel graphical user interface applications designed to strengthen foundational knowledge in audio, image, and video signal coding. These interactive tools, specifically developed for use in university courses, allow students to experiment with various coding techniques, providing hands-on experience that bridges theoretical concepts and practical application. Furthermore, we propose a robust methodology to evaluate the effectiveness of these tools in improving learning outcomes. The tools, developed using MATLAB, were integrated into a computer vision course and assessed through a combination of pre- and post-tests, the System Usability Scale, and the Evaluation Tool for Learning Quality. Results indicate a significant improvement in student knowledge and positive feedback regarding the usability and educational value of the tools. These findings suggest that the interactive nature of the tools not only enhances knowledge retention but also boosts student engagement, offering a valuable complement to traditional educational methods in higher education.